PERAN GURU BIMBINGAN KONSELING DAN GURU AQIDAH AKHLAK DALAM MENGATASI PERMASALAHAN SISWA - Ummah, Nasihatul; Umam, Khoirul (Al Tadib : Jurnal Ilmu Pendidikan, 2022)
This study discusses the role of counseling guidance teachers and the role of moral aqidah teachers in overcoming student problems and the supporting and inhibiting factors of Counseling Guidance teachers and Aqidah Akhlak teachers in overcoming student problems at MTsN 1 Jombang. This research is a case study research using a qualitative approach with technical data collection observations, interviews and documentation. While the data analysis techniques are data reduction techniques, data presentation and verification. The results of research that have been carried out regarding the role of BK teachers and Aqidah Akhlak teachers in overcoming student problems at MTsN 1 Jomabng. So it is necessary for the role of Guidance Counseling teachers and Aqidah teachers in addressing these problems so that students can comply with school regulations according to existing regulations and become a good generation by not doing actions that are not according to the norm. Therefore, assistance is needed in the growth and development of students. The supporting factors in this case are all parties to play an active role in helping to overcome student problems, all have one vision and mission, maintain the name of a good school environment, and the cooperation of all teachers with the homeroom teacher. as the main implementer in helping to alleviate student problems.